Thrombotic Pathology in Placenta of COVID Positive Pregnancy - Baral, Gehanath; Shrestha, Oshan; Baral, Reetu Sharma (Journal of Nepal Health Research Council, 2021)
Covid positive pregnant women were increasingly getting delivery in the health institution. Most of them were asymptomatic and had positive report after their obstetric event was over because of emergency nature of care. Lack of autopsy is the lacunae in determining tissue pathology. One case of sudden intrauterine fetal death in Covid positive patient had induced delivery in the hospital and the placental histopathology examination showed widespread villous infarction, decidual arteriopathy with thrombosis and chorioamnionitis.Keywords: Covid positive; fetal death; placenta; thrombosis